2002
DOI: 10.1093/emboj/cdf653
|View full text |Cite
|
Sign up to set email alerts
|

BSE prions propagate as either variant CJD-like or sporadic CJD-like prion strains in transgenic mice expressing human prion protein

Abstract: Variant Creutzfeldt-Jakob disease (vCJD) has been recognized to date only in individuals homozygous for methionine at PRNP codon 129. Here we show that transgenic mice expressing human PrP methionine 129, inoculated with either bovine spongiform encephalopathy (BSE) or variant CJD prions, may develop the neuropathological and molecular phenotype of vCJD, consistent with these diseases being caused by the same prion strain. Surprisingly, however, BSE transmission to these transgenic mice, in addition to produci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
355
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 329 publications
(383 citation statements)
references
References 33 publications
25
355
0
3
Order By: Relevance
“…Experimental confirmation that variant CreutzfeldtJakob disease (vCJD) [1] is caused by the same prion strain as that causing bovine spongiform encephalopathy (BSE) in cattle [2][3][4][5] led to global concern that human exposure to BSE prions posed a significant threat to public health [6][7][8]. While the risk of new dietary exposure to BSE prions in the UK is now remote [9], the majority of the UK population may have been exposed during the late 1980s and early 1990s.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental confirmation that variant CreutzfeldtJakob disease (vCJD) [1] is caused by the same prion strain as that causing bovine spongiform encephalopathy (BSE) in cattle [2][3][4][5] led to global concern that human exposure to BSE prions posed a significant threat to public health [6][7][8]. While the risk of new dietary exposure to BSE prions in the UK is now remote [9], the majority of the UK population may have been exposed during the late 1980s and early 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the paucity of tissue available, it was not possible to inoculate different lines of transgenic mice expressing either human PrP 129 methionine or valine. Based on our experience of the transmission properties of vCJD and BSE prions, we chose to use Tg45 mice homozygous for 129 methionine [5]. These mice faithfully propagate the molecular and neuropathological phenotype of vCJD following primary challenge with either vCJD prions [5,57] or BSE prions [5] and are known to be sensitive to infection when inoculated with vCJD peripheral tissue containing PrP Sc at a concentration 10 4.7 -fold lower than in brain [57].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…-mapping PrP regions involved in or required for PrP conversion and prion replication [36,37,44,56,57,63,78,80]; -studies on the physiological role of PrP C and the contributions of individual molecular regions to these functions [65]; -studies on molecular aspects of species barrier effects by mutation of single or limited numbers of positions within the PrP [20,41,51,76,77,82]; -modelling of familial forms of human prion diseases [3,4,60]; -analysis of the cell specificity of prion propagation [48,71,72]; -analysis of the role of PrP glycosylation [22,64]; -studies on the mechanisms of prion spread [11,12]; -studies on the neuropathological roles of PrP C and of PrP D in prion disease [39]; -studies on the function of PrP Doppel [34].…”
Section: Mutant Prp Expression Modelsmentioning
confidence: 99%
“…represented only one defined strain when reisolated from a variety of species (including vCJD in humans) which were infected during the course of the BSE epidemic in the UK. Asante et al [3] have reported that the transmission of BSE to Tg35 mice overexpressing human PrP C produced primarily the well known vCJD PrP D phenotype, but also in low numbers a second phenotype (distinguished by biochemical and anatomical analysis of the PrP D deposits) which was reminiscent of sporadic CJD PrP D . Another publication describes the transmission of a new bovine prion strain called bovine amyloidotic spongiform encephalopathy (BASE), which can be discriminated from BSE mainly on the basis of a lower molecular mass of the unglycosylated form of PrP D , a different anatomical distribution of the accumulated PrP D in the brain, and by the presence of PrP immunoreactive amyloid plaques, bovine PrP transgenic mice.…”
Section: Phenotypic And/or Biological Evolution Of Prion Strains As Amentioning
confidence: 99%